Entrepreneurship Learning and Training Model Business Canvas Model as a Stimulant for Santri Entrepreneurial Interest - Fauzan Muttaqien; Mokhamad Taufik; Kasno Kasno; Danang Wikan Carito (Innovation Business Management and Accounting Journal, 2022)
The tendency of entrepreneurial interest can grow from an early age, especially in the world of education because of a systematic learning process. Previous studies stated that entrepreneurial interest can be carried out through the right learning system in the field of entrepreneurship studies and effective training on entrepreneurship. This shows that aspects of theoretical science and applied science and practice must be in synergy. Previous research provides empirical evidence that the Business Canvas Model (BCM) entrepreneurship learning model and entrepreneurship training have an effect on the growth of entrepreneurial interest in higher education. The research was conducted at Miftahul Midad Islamic Boarding School, Lumajang Regency. Primary data obtained from the distribution of questionnaires were analyzed by multiple linear regression test. The results showed that the Business Canvas Model (BCM) entrepreneurship learning model and entrepreneurship training had an effect on interest in entrepreneurship. Because of the large influence of learning and entrepreneurship training on students' interest in entrepreneurship, an appropriate and systematic model is needed to stimulate them to become competent entrepreneurs.